Hyperglycemia and chronic diabetic complications - Ahmad H Asdie, Ahmad H Asdie (Universitas Gadjah Mada, 1987)
The paper presented a brief review of the role of hyperglycemia in the development of complications in the diabetic patient. The chronic diabetic complications tend to occur in patients with longstanding diseases. Althoueh the exact mechanism responsible for the development of each complication is not fully clarified, the [actors such as accumulation 01 soronol derived from hyperglycemia through polyol pathway, glycoproteins, myo-inositol deficiency, glycosylated non-enzymatic proteins, ketogenesis, hyperlipidemia, increased adhesiveness of platelet and hyperviscocity are thought to play significant roles in the pathogenesis. If the degree of metabolic abnormalities can be reduced by dietary manipulation and insulin administration, the rate of development of diabetic complications should also be reduced. This hypothesis has been shown to be correct by several investigators. Others disagree with that. However, whatever the cause of the development of chronic diabetic complications were it is believed that diabetic control is important and that each diabetic patient should be encouraged to learn as much as possible about diabetes mellitus in that they will have a better understanding of the necessity as well as the desire for good control. If complete normalization of blood glucose and other metabolic abnormalities can not be achieved, the chronic diabetic complications will continue to occur. And in the severe cases, the result of the treatment may not influence the nature of the complications. Key Words: hyperglycemia - chronic diabetic complications - polyol pathway - glycosylated non-enzymatic proteins - metabolic abnormalities